PENGARUH SANKSI ADAT MENTAWAI TERHADAP TINGKAT KEBERHASILAN PENYIDIKAN TINDAK PIDANA KESUSILAAN DENGAN KORBAN ANAK - Nofri, Nofri (UNES Journal of Swara Justisia, 2018)
The investigation was carried out to gather sufficient evidence that a crime had indeedtaken place. In the Mentawai area there are cases of decency crime with child victimsresolved by giving customary sanctions to the perpetrators. This research is legal researchwith analytical descriptive specifications. Investigation of decency crime by SatreskrimMentawai Islands Resort Police is carried out by receiving reports from victims and / ortheir families, victims placed in Special Service Rooms (RPK), then inspected, cooperatedwith psychiatrists, and providing shelter for victims Regarding the case of decency towardsthe child that has been reported and the investigation begins if it has been resolved bycustom, the parties will ask the investigator to stop the investigation. The obstacles ininvestigating the Mentawai Islands geographical factors which consist of many islands andthe difficulty of inter-island transportation have led to investigations sometimes having tobe carried out for a long time. was stopped because it had been resolved by custom andrequested by the local government to be stopped by the investigation process.